2013
DOI: 10.1080/13611267.2013.855860
|View full text |Cite
|
Sign up to set email alerts
|

College Women Mentoring Adolescent Girls: The Relationship between Mentor Peer Support and Mentee Outcomes

Abstract: In this study, we examined the effectiveness of peer support for college women mentors who engaged in one-to-one and group mentoring with at-risk adolescent girls. Using data from 162 mentoring pairs, results suggested that mentor support positively predicted mentees' self-reported improvement after a year of mentoring. An examination of mentees' selfesteem outcomes revealed that mentor peer support was associated with higher outcomes only for those mentees who had higher pre-program scores; for those with bel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 40 publications
(52 reference statements)
0
1
0
Order By: Relevance
“…The authors concluded that mentors may have contacted staff only when their relationships were struggling (DuBois & Neville, ), though this was not yet evidenced. A more recent finding showed that mentors’ perception of support from their mentor peers may actually have negative effects for mentees who begin the program with low self‐esteem (Marshalla, Lawrencea, & Peugha, ). Taken together, these results may indicate that mentor support is not always effective, but it may also indicate that findings on the effectiveness of mentor support depend on the way in which it is measured.…”
Section: Mentor Supportmentioning
confidence: 99%
“…The authors concluded that mentors may have contacted staff only when their relationships were struggling (DuBois & Neville, ), though this was not yet evidenced. A more recent finding showed that mentors’ perception of support from their mentor peers may actually have negative effects for mentees who begin the program with low self‐esteem (Marshalla, Lawrencea, & Peugha, ). Taken together, these results may indicate that mentor support is not always effective, but it may also indicate that findings on the effectiveness of mentor support depend on the way in which it is measured.…”
Section: Mentor Supportmentioning
confidence: 99%